2020
DOI: 10.1155/2020/8842091
|View full text |Cite
|
Sign up to set email alerts
|

Analysis on the Triaxial Shear Behavior and Microstructure of Cement‐Stabilized Clay Reinforced with Glass Fibers

Abstract: A series of triaxial compression tests were conducted to investigate the influence of the fiber content and confining pressure on the shearing characteristics of cement-stabilized clay reinforced with glass fibers. The glass fiber contents were 0, 1‰, 2‰, 3‰, and 4‰ by weight of the dry soil. The stress strain and volume change behavior, shear strength, and energy absorption of the test specimen were obtained. The results indicate that the inclusion of glass fibers can increase the shear strength, inhibit the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…The observed increase in liquid limit (LL) with higher sisal fiber content can be attributed to the water absorption capacity of sisal. This observation aligns with findings reported by Sani et al, [40] and Bo et al, [41]. On the two treatment methods used, It could be observed that soil treated with plastic strips-cement mix recorded slightly lower liquid limit values when compared with samples treated with sisal fiber.…”
Section: Effect Of Plastic Strips/sisal Fiber and Cement On The Liqui...supporting
confidence: 91%
“…The observed increase in liquid limit (LL) with higher sisal fiber content can be attributed to the water absorption capacity of sisal. This observation aligns with findings reported by Sani et al, [40] and Bo et al, [41]. On the two treatment methods used, It could be observed that soil treated with plastic strips-cement mix recorded slightly lower liquid limit values when compared with samples treated with sisal fiber.…”
Section: Effect Of Plastic Strips/sisal Fiber and Cement On The Liqui...supporting
confidence: 91%
“…Since, CBR value at 2.5 mm penetration is often greater than CBR value at 5 mm penetration, it is usually preferred in pavement design. The test is repeated one more time when CBR value at 5 mm penetration is found to be greater than that at 2.5mm penetration [26]. Fig.…”
Section: Unconfined Compressive Strength Characteristicsmentioning
confidence: 99%
“…Because clayey soils volume change behavior is so sensitive to moisture content, expansive soils are used difficult in engineering applications [2]. A variety of soil stabilization techniques have been used to stabilize expansive soil, including fly ash [11] RBI Grade-81 [12], Steel fiber [13], Rice husk [14], glass fiber [15][16][17][18][19][20][21][22][23][24][25][26], bagasse ash [4] [27-28], lime [27, [29][30], cement [26,31], corn straw ash [32], Polypropylene Fiber [10,18,33], Basalt Fiber [34], Coir Fiber [35], Sisal Fibre [36], Jute Fiber [37] and Plastic Waste Powder [38] etc. When the area to be treated is limited, reinforcements are especially trustworthy and successful at strengthening weak soil.…”
Section: Introductionmentioning
confidence: 99%
“…Their results and those of many other researchers, such as Tong et al (2019) et al, show that the shear strength of clay with fibers increases with increasing fiber content and that the cohesion and internal friction angle of the clay increase with reinforcement. According to Qu and Sun (2016) and Ruan et al (2020), cohesive soils reinforced with fiber exhibit less expansibility as the fiber concentration increases. Yang et al (2023) proved that when the mass per unit area of the geotextile increased, the interface friction between the soil and geotextile increased, and the cracking of the soil was effectively inhibited.…”
mentioning
confidence: 99%